Language Features Found in Essays About Madurese Art - PUTRI, SHEILA AYU RIRIS ANDIKA; Al Rosyiidah, Afiifah (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2024)
This study aims to examine and explain language features in essays about Madurese arts. The writers uses qualitative descriptive methods to elaborate data. The source of the data in this study is essays by second semester students of English Department at Universitas Trunojoyo Madura which discuss about Madurese art. Meanwhile, the data of this study are characters, sentences, and paragraphs in essays that contain various language features. This study uses Gerot and Wignell (1995) theory of language features in descriptive essays. The result of this study shows that there are five language features that students use in their essays: the use of certain objects, the use of simple present tense, the use of noun and adjective phrases, the use of auxiliary, and the use of linking verb.